Understanding barriers for pregnant women, especially those who might be HIV positive, to deliver at a clinic : a research case of Kuajok Health Care Clinic in Gogrial West County - Warrap State, South Sudan - Shamamba-Kinyungu, Leonardo (Stellenbosch : Stellenbosch University, 2013)
Thesis (MPhil)--Stellenbosch University, 2013.